STN-DBS Reduces Saccadic Hypometria but Not Visuospatial Bias in Parkinson's Disease Patients - Fischer, Petra; Ossandón, José P.; Keyser, Johannes; Gulberti, Alessandro; Wilming, Niklas; Hamel, Wolfgang; Köppen, Johannes; Buhmann, Carsten; Westphal, Manfred; Gerloff, Christian; Moll, Christian K. E.; Engel, Andreas K.; et al. (Frontiers in Behavioral Neuroscience, 2016)
In contrast to its well-established role in alleviating skeleto-motor symptoms in Parkinson´s disease, little is known about the impact of deep brain stimulation (DBS) of the subthalamic nucleus (STN) on oculomotor control and attention. Eye-tracking data of 17 patients with left-hemibody symptom onset was compared with 17 age- matched control subjects. Free-viewing of natural images was assessed without stimulation as baseline and during bilateral DBS. To examine the involvement of ventral STN territories in oculomotion and spatial attention, we employed unilateral stimulation via the left and right ventralmost contacts respectively. When DBS was off, patients showed shorter saccades and a rightward viewing bias compared with controls. Bilateral stimulation in therapeutic settings improved saccadic hypometria but not the visuospatial bias. At a group level, unilateral ventral stimulation yielded no consistent effects. However, the evaluation of electrode position within normalized MNI coordinate space revealed that the extent of early exploration bias correlated with the precise stimulation site within the left subthalamic area. These results suggest that oculomotor impairments but not higher-level exploration patterns are effectively ameliorable by DBS in therapeutic settings. Our findings highlight the relevance of the STN topography in selecting contacts for chronic stimulation especially upon appearance of visuospatial attention deficits.